2018
DOI: 10.3847/1538-4357/aae833
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Signal Loss in the 21 cm Reionization Power Spectrum: A Revised Study of PAPER-64

Abstract: The Epoch of Reionization (EoR) is an uncharted era in our Universe's history during which the birth of the first stars and galaxies led to the ionization of neutral hydrogen in the intergalactic medium. There are many experiments investigating the EoR by tracing the 21 cm line of neutral hydrogen. Because this signal is very faint and difficult to isolate, it is crucial to develop analysis techniques that maximize sensitivity and suppress contaminants in data. It is also imperative to understand the trade-off… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 75 publications
0
90
0
Order By: Relevance
“…Paciga et al 2013) and power spectra estimation (e.g. Cheng et al 2018;Kolopanis et al 2019). To ensure limited signal loss or bias of the 21-cm signal power spectra, a number of checks were performed at various steps in the processing pipeline.…”
Section: Data-processing Cross-checksmentioning
confidence: 99%
“…Paciga et al 2013) and power spectra estimation (e.g. Cheng et al 2018;Kolopanis et al 2019). To ensure limited signal loss or bias of the 21-cm signal power spectra, a number of checks were performed at various steps in the processing pipeline.…”
Section: Data-processing Cross-checksmentioning
confidence: 99%
“…This is one measure of the uncertainty on the power spectra due to noise, but also represents the theoretical amplitude of the power spectra in the limit that they are noise dominated (as opposed to signal or systematic dominated). This is given in Cheng et al (2018) as…”
Section: Power Spectrum Performancementioning
confidence: 99%
“…One of the only direct probes of the IGM throughout the entirety of Cosmic Dawn is neutral hydrogen's 21 cm transition, which at redshifts of z ∼ 10 appears in the low-frequency radio band around 150 MHz. Over the past decade, first-generation 21 cm EoR experiments like the Donald C. Backer Precision Array for Probing the Epoch of Reionization (PAPER; Parsons et al 2014;Jacobs et al 2015;Cheng et al 2018;Kolopanis et al 2019), the Murchison Widefield Array (MWA; Tingay et al 2013;Dillon et al 2014;Beardsley et al 2016;Barry et al 2019b;Li et al 2019), the Low Frequency Array (LOFAR; van Haarlem et al 2013;Patil et al 2017;Gehlot et al 2019), the Giant Metre Wave Radio Telescope (GMRT; Paciga et al 2013), and the Long Wavelength Array (LWA; Eastwood et al 2019) have set increasing stringent limits on the Cosmic Dawn 21 cm power spectrum. Meanwhile, global signal experiments have placed constraints on the 21 cm monopole (Bernardi et al 2016;Singh et al 2017), with a reported first detection of the signal at Cosmic Dawn from the Experiment to Detect the Global EoR Signature (EDGES; Bowman et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We now turn our attention to another systematic we refer to as antenna cross coupling, which acts to couple one antenna's voltage stream with another antenna's voltage stream before reaching the correlation stage. Note that our model for cross coupling is different than "capacitive crosstalk" created by the electric field of two parallel signal chains interacting with each other within cabling, receivers, and analogue-to-digital conversion (ADC) units, which is a common systematic for radio interferometers (Parsons & Backer 2009;Zheng et al 2014;Ali et al 2015;Patil et al 2017;Cheng et al 2018). There are well established hardware solutions for suppressing crosstalk, such as phase switching (Chaudhari et al 2017).…”
Section: Describing Antenna Cross Couplingmentioning
confidence: 99%